Perancangan Ulang Tata Letak Gudang Bahan Baku Menggunakan Metode Class-Based Storage dan Integrasi RFID-WMS di PT. XYZ - Jumiono, Aji; Anggraeni, Ratih (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2025)
Warehouse layout has a crucial role in supporting material flow efficiency and operational cost control in internal logistics activities. The purpose of this research is to redesign the layout of raw material warehouses using the data-based CBS method , as well as integrate it with a WMS system based on RFID technology, in order to improve operational efficiency, stock management accuracy, and support sustainability and productivity in the food industry. The method in this study uses a Class-Based Storage (CBS) approach integrated with a Warehouse Management System (WMS) based on RFID technology. The results showed that the 5th alternative layout provided the best performance with an Adjacency Score of 0.39 and was able to reduce the total daily displacement distance from 1,091.5 meters to 656 meters (a decrease of 39.9%). This efficiency has an impact on reducing daily material handling costs of IDR 2,146,915 (44.16%). The additional area of 1,110 m² is used for strategic zone arrangement such as loading docks, raw materials, and production preparation areas. The integration of the RFID system with the Warehouse Management System (WMS) also increases the accuracy of stock recording from 74.35% to 89.17%. These findings show that the use of spatial data, activity analysis, and integrated technology can improve logistics efficiency and support the smooth operation of warehouses.